Subjective norms and behavioral control in using ChatGPT for learning: A comparative explanatory case study - Addun, Beverly M; Nozaleda, Bryan M (Journal of Education and e-Learning Research, 2026)
This study demonstrates how social demands and perceived control differently translate into transactional versus introspective engagement with ChatGPT, contextualizing the Theory of Planned Behavior. Using a previous cluster analysis of 279 students, a comparative explanatory case study was carried out. From the separate focus group discussions, four subjective norm themes emerged, including academic pressures, ethical concerns, social and environmental influences, and technological accessibility. Meanwhile, four behavioral control themes surfaced, including collaborative/supportive role, contextual use, knowledge and inspiration, and utilitarian usage. Academic demands were highlighted in both clusters, although Cluster 2 was more motivated by the availability of technology and showed utilitarian usage as the predominant control pattern. Cluster 1 placed more importance on ethical issues and relied less on ChatGPT for utilitarian goals, mostly for inspiration and collaborative purposes. The study concludes that social expectations, ethical awareness, and situational control interact dynamically in students' use of ChatGPT. Depending on the cluster, reflective, guided learning coexists with utilitarian, assignment-driven utilization. Therefore, there must be a balance between efficiency and accessibility, as well as morality and critical thinking, in our educational solutions. In action, scaffolding selective and guided applications of ChatGPT is a step further in integrating ethical and critical AI literacy into curricula.